Incidental cytokeratin-positive interstitial reticulum cell tumor of the lymph node accompanied by breast cancer: Status of YAP/TAZ expression in tumor cells - Chiemi Saigo; Yusuke Kito; Masayoshi Hasegawa; Shusuke Nomura; Takuya Mikamo; Yuki Hanamatsu; Ryutaro Mori; Manabu Futamura; Kazuhiro Yoshida; Tamotsu Takeuchi (Elsevier, 2021)
Approximately 24 cases of cytokeratin-positive interstitial reticulum cell tumors have been reported in English literature. In this paper, we report a case of cytokeratin-positive interstitial reticulum cell tumor that was localized in the parafollicular region of the axillary lymph node and was an incidental finding in a patient with breast cancer. A 50 year-old woman underwent a mastectomy and lymph node dissection following a preoperative diagnosis of bilateral breast cancer. Histopathological examination revealed that the patient had non-invasive and invasive ductal carcinoma in the right and left mammary glands. Although we could not detect breast cancer metastasis in the lymph nodes, one of eight right axillary lymph nodes harbored an 11 × 8 mm discohesive sheet of large polygonal epithelioid tumor cells in the parafollicular area. Tumor cells were immunoreactive for AE1/AE3, CAM5.2, CK18 and l-caldesmon and negative for CD1a, CD21, CD23, CD31, CD68, and S‑100 protein markers. Based on these findings, the lesion was diagnosed as a cytokeratin-positive interstitial reticulum cell tumor of the lymph node. Notably, this early-stage cytokeratin-positive interstitial reticulum cell tumor demonstrated focal nuclear YAP/TAZ proto-oncogene products, which were recently identified as critical for differentiation, maturation, and function of fibroblastic reticular cells. To the best of our knowledge, this is the first report to describe nuclear YAP/TAZ immunoreactivity in cytokeratin-positive interstitial reticulum cell tumors.